Representations of Islamic fundamentalism and the Ahmed Zaoui ease - Brown, Malcolm (Islam and Christian-Muslim relations, 2010)
This article takes the form of an abridged and annotated version of an affidavit that I wrote in support of Ahmed Zaoui, an Algerian refugee who spent 10 months in solitary confinement in New Zealand. Its central aims are to reflect sociologically on some of the issues that were at stake in this case, within the context of an analysis of Islamic fundamentalism as a specific synthesis of traditionalist and liberal Islam. I observe that fundamentalism is often analysed in terms of a ‘failure’ to recognize or value the products of modernity and mysticism, even in academic discourses, and that its use is vitiated by a negative evaluation of fundamentalism prior to the point of definition. Furthermore, the understanding of Islamic fundamentalism is central to Western perceptions and fears of Islam, and, specifically, to the allegations of the New Zealand SIS (Security and Intelligence Service) against Zaoui; the case turned around the question of whether or not he was an Islamic fundamentalist. This case therefore shows that the sociological analysis of terms such as Islamic fundamentalism has a real bearing on people's lives, and is not merely a conceptual or theological discussion that occurs within the ivory towers.